Determinant of design elements and compositional settings of window display on the corporate strategic merchandising of large scale department store: a case of central world department store - Thitipann Kernsom; Nopadon Sahachaisaeree (My University, 2010)
Abstract Utilizing window display arrangements in the Central World Department Store in Bangkok as a case study, the research aims to elucidate the differentiation of design settings in attracting and conveying of merchandizing message to its target group. The research hypothesizes that the manipulation of window display design elements is able to convey the product positioning, value, and quality correctly. A set of 3D photographic stimulus with different design element is created to test with a group of 200 subjects for perceptual response and decision to purchase. Findings of the experiment are utilized to model the window display design principle.
Keywords: Color perception and design